Salicylic Acid, Jasmonate, and Ethylene Contribute to Rice Defense Against White Tip Nematodes Aphelenchoides besseyi - Xie, Jialian; Yang, Fang; Xu, Xing; Peng, Yunliang; Ji, Hongli (Frontiers in Plant Science, 2022)
Plant hormones have a prominent place in plant immune and defence mechanism. To gain more information about the plant hormone pathways involved in rice defence against nematodes, here we studied the roles of three core hormones including salicylic acid (SA), jasmonate (JA), and ethylene (ET) in rice defence to Aphelenchoides besseyi by using the susceptible variety Nipponbare as well as the resistant variety Tetep. The data showed that Tetep exhibited pre- and post-invasion with suppression of nematode infection, development and reproduction. The qRT-PCR analysis of plant hormone marker genes in the two cultivars clearly revealed that all the SA related genes were down-regulated in susceptible Nipponbare plants but were significantly up-regulated in resistant Tetep plants at flowering stage. Exogenous application of the SA analog BTH, methyl jasmonate (MeJA) and ethephon did induce rice resistance to A. besseyi, and the inhibitors of these hormones treated plants increased susceptibility to A. besseyi. Similarly, corresponding transgenic biosynthesis or signaling mutants of those hormones showed increased susceptibility as well. Collectively, these results suggest that SA, JA and ET play important defence roles in rice against A. besseyi.